Advances in the thermo-chemical production of hydrogen from biomass and residual wastes: Summary of recent techno-economic analyses. (March 2020) - Shahabuddin, M.; Krishna, Bhavya B.; Bhaskar, Thallada; Perkins, Greg
Highlights: Recent advances in gasification and pyrolysis followed by reforming are reviewed. The levelized cost of hydrogen (LCOH) from biomass is 2.3 to 5.2 USD/kg. The LCOH from residual wastes are estimated to be 1.4 to 4.8 USD/kg. Technical barriers are waste pre-treatment, syngas conditioning, technology scale. Socio-economic barriers are hydrogen market, technology competitiveness, policies. Abstract: This article outlines the prospects and challenges of hydrogen production from biomass and residual wastes, such as municipal solid waste. Recent advances in gasification and pyrolysis followed by reforming are discussed. The review finds that the thermal efficiency of hydrogen from gasification is 50%. The levelized cost of hydrogen (LCOH) from biomass varies from 2.3–5.2 USD/kg at feedstock processing scales of 10 MWth to 2.8–3.4 USD/kg at scales above 250 MWth. Preliminary estimates are that the LCOH from residual wastes could be in the range of 1.4–4.8 USD/kg, depending upon the waste gate fee and project scale. The main barriers to development of waste to hydrogen projects include: waste pre-treatment, technology maturity, syngas conditioning, the market for clean hydrogen, policies to incentivize pioneer projects and technology competitiveness. The main opportunity is to produce low cost clean hydrogen, which is competitive with alternative production routes.